Job satisfaction of Spanish knowledge-based workers: Characterization and determinants - Jackeline Velazco Portocarrero; Joan Torrent Sellens; Clara Vi\~nas-Bardolet (Internet Interdisciplinary Institute, Open University of Catalonia (UOC), 2014)
The aim of the working paper is to address the characterization and determinants of job satisfaction for knowledge-based workers in Spain. To do this, micro data of 8,061 workers from the 2010 Survey of Quality of Life at Work was used for empirical analysis. Regarding job satisfaction, the variable was approximated by declared worker satisfaction, measured on a scale of 0 to 10, from total dissatisfaction to complete satisfaction. It is observed that only a small fraction of Spanish workers are explicitly dissatisfied. 61.3% of knowledge-based workers report very satisfied job satisfaction (levels 8 to 10). 41.4% of the less knowledge-based report satisfied job satisfaction (levels 5 to 7). An ordered probit model, which is designed to model the choice between discrete alternatives, was preferred for the determinants analysis. Evidence suggests that financial and non-financial (work organisation and work intensity) job dimensions are the most important determinants of knowledge-based workers satisfaction in Spain. In particular, job satisfaction in knowledge-based workers is basically explained by satisfaction with salary, level of motivation, career advancement, manager's evaluation, relationships between managers and employees, satisfaction with working hours, and satisfaction with job security. Additionally, stress and risk levels have negative effects.
Keywords: J24; J28; J81; 330; knowledge-based work; Job satisfaction; Work organisation; Work intensity